Heritability of aggressive behavior in selected cultural groups in Mindanao, Philippines - Demayo,Cesar G. (INSInet Publications, 2011)
Mindanao, considered as one of the least peaceful part of the country, has been an interesting site for the study of aggression, an intentional act that is directed toward another individual with the goal of inflicting harm or injury. With Mindanao's high ethnic diversity, this study was conducted to determine the heritability and the variability of aggressive behavior among selected groups in Mindanao, specifically the Maranao, Cebuano, Boholano, Ilocano, Ilonggo, Bicolano, Chavacano and Butuanon. The data were gathered from the 240 family respondents from selected areas in Mindanao with the aid of the Buss-Perry Aggression Questionnaire.The Analysis of Variance (ANOVA) and the Box plot were used to analyze the variability of aggression among the eight cultural groups in the four subtypes of aggression:Anger, Hostility, Verbal Aggression and Physical Aggression. The ANOVA test showed significant difference in hostility and physical aggression among the groups while the box plot analysis showed the Ilonggos as the group being the most hostile and most physically aggressive, followed by the Maranao group. For the heritability of aggression, the correlation analysis was used between the paired up mother-daughter, mother-son, father-daughter, and father-son. Some pairs among the different cultural groups showed a positive correlation while other pairs showed low or no correlation at all. The positive correlation indicated the genetic basis of the aggression while the low correlation or no correlation indicated the strong environmental influence on human in Mindanao.